Solve for P Q=25-P

Math
Q=25-P
Rewrite the equation as 25-P=Q.
25-P=Q
Subtract 25 from both sides of the equation.
-P=Q-25
Multiply each term in -P=Q-25 by -1
Tap for more steps…
Multiply each term in -P=Q-25 by -1.
(-P)⋅-1=Q⋅-1+(-25)⋅-1
Multiply (-P)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1P=Q⋅-1+(-25)⋅-1
Multiply P by 1.
P=Q⋅-1+(-25)⋅-1
P=Q⋅-1+(-25)⋅-1
Simplify each term.
Tap for more steps…
Move -1 to the left of Q.
P=-1⋅Q+(-25)⋅-1
Rewrite -1Q as -Q.
P=-Q+(-25)⋅-1
Multiply -25 by -1.
P=-Q+25
P=-Q+25
P=-Q+25
Solve for P Q=25-P

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top